2020
DOI: 10.3390/ma13194324
|View full text |Cite
|
Sign up to set email alerts
|

Slicing Ceramics on Material Removed by a Single Abrasive Particle

Abstract: Multi-wire saw machining (MWSM) used for slicing hard-brittle materials in the semiconductor and photovoltaic industries is an important and efficient material removal process that uses free abrasives. The cutting model of single-wire saw machining (SWSM) is the basis of MWSM. The material removal mechanism of SWSM is more easily understood than MWSM. A mathematical model (includes brittle fracture and plastic deformation) is presented in this paper for SWSM ceramic with abrasives. This paper determines the ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Bidiville et al [13] found that a low abrasive volume fraction in the slurry, a low wire tension, and a slow feed rate can obtain the strongest wafers in a slicing silicon wafer. Tsai et al [14] reported wire speed and working load are positively correlated with material removal of single-wire saw machining ceramics. A review of some papers on the system and process level investigations for both multi-wire slurry sawing and diamond wire-sawing is also presented in Reference [15].…”
Section: Introductionmentioning
confidence: 99%
“…Bidiville et al [13] found that a low abrasive volume fraction in the slurry, a low wire tension, and a slow feed rate can obtain the strongest wafers in a slicing silicon wafer. Tsai et al [14] reported wire speed and working load are positively correlated with material removal of single-wire saw machining ceramics. A review of some papers on the system and process level investigations for both multi-wire slurry sawing and diamond wire-sawing is also presented in Reference [15].…”
Section: Introductionmentioning
confidence: 99%